DINAMIKA SOSIAL DAN MEDIASI KONFLIK DALAM TRADISI SEDEKAH LAUT DI DESA PERLIS, KECAMATAN BRANDAN BARAT, KABUPATEN LANGKAT - Hardiyanti, Siti; Nasution, Abdullah Akhyar; Ilham, Iromi; Husen, M.; Novianti, Novianti (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2025)
This study analyses the pattern of social interaction in conflict resolution of the sea alms tradition in Perlis Village, West Brandan District, Langkat Regency. The sea alms tradition, which has been practiced across generations, has been rejected by the Majelis Taklim group, which considers it a practice that is contrary to Islamic teachings. This study uses a qualitative method with a descriptive approach. This study analyses the roles of the actors involved and the patterns of interaction in conflict resolution efforts through mediation. Data collection was done through observation, interviews, and document studies. The results showed that the conflict was a value conflict, which was then resolved through mediation. The pattern of social interaction applied uses an accommodation approach in the form of compromise and conciliation, which results in an agreement to continue implementing the tradition by eliminating elements considered contrary to Islamic value.